Cultural Construction of Empire : the U.S. Army in Arizona and New Mexico. - Lahti, Janne (UNP - Nebraska, 2012)
From 1866 through 1886, the U.S. Army occupied southern Arizona and New Mexico in an attempt to claim it for settlement by Americans. Through a postcolonial lens, Janne Lahti examines the army, its officers, their wives, and the enlisted men as agents of an American empire whose mission was to serve as a group of colonizers engaged in ideological as well as military, conquest. Cultural Construction of Empire explores the cultural and social representations of Native Americans, Hispanics, and frontiersmen constructed by the officers, enlisted men, and their dependents.